Distribution of Pyrogenic Carbon in the Soil of a Cold Temperate Coniferous Forest 13 Years After a Severe Wildfire - Lina Shi; Yuanchun Peng; Xingyu Hou; Yun Zhang (Land)
Biomass combustion produces between 50 and 270 Tg of pyrogenic carbon (PyC) annually. PyC is extremely highly stable, making it a significant component of the global carbon sink. We established four plots at different slope positions within a cold temperate coniferous forest that experienced a severe fire in 2010. We mechanically divided the soil into three depths. The PyC content and density of the collected soil samples and four particle sizes were analyzed. Thirteen years after the fire, the PyC content in the soil on the upper slope was low (13.5–14.2 g·kg−1). In terms of PyC density, the valley and the upper slopes presented lower values. The PyC content in the 0~10 cm layer (14.0–16.7 g·kg−1) is only slightly more than 20% higher than that in the two deeper layers, whereas its density is 1.5~2 times more than that in the other layers. Our findings indicate that PyC is predominantly concentrated in coarse sand and silt particles. The spatial pattern of PyC is significantly influenced by the differentiation in topography, soil layer depth, and particle size. These distribution patterns strongly show that PyC plays a key role in forest ecosystem cycles affected by fire. PyC distribution in particle sizes particularly shows connections with specific soil components. There is a synergistic effect between the topographic redistribution (slope position differences), vertical stratification (soil depth), and particle size sorting of PyC. This determines the retention effect of stable carbon in fire-disturbed forest ecosystem soils, thereby influencing the soil carbon cycle.